Extratubular Polymerized Uromodulin Induces Leukocyte Recruitment and Inflammation In Vivo - Immler, Roland; Lange-Sperandio, Bärbel; Steffen, Tobias; Beck, Heike; Rohwedder, Ina; Roth, Jonas; Napoli, Matteo; Hupel, Georg; Pfister, Frederik; Popper, Bastian; Uhl, Bernd; Mannell, Hanna; et al. (Frontiers in Immunology, 2020)
Uromodulin (UMOD) is produced and secreted by tubular epithelial cells. Secreted UMOD polymerizes (pUMOD) in the tubular lumen, where it regulates salt transport and protects the kidney from bacteria and stone formation. Under various pathological conditions, pUMOD accumulates within the tubular lumen and reaches extratubular sites where it may interact with renal interstitial cells. Here, we investigated the potential of extratubular pUMOD to act as a damage associated molecular pattern (DAMP) molecule thereby creating local inflammation. We found that intrascrotal and intraperitoneal injection of pUMOD induced leukocyte recruitment in vivo and led to TNF-α secretion by F4/80 positive macrophages. Additionally, pUMOD directly affected vascular permeability and increased neutrophil extravasation independent of macrophage-released TNF-α. Interestingly, pUMOD displayed no chemotactic properties on neutrophils, did not directly activate β2 integrins and did not upregulate adhesion molecules on endothelial cells. In obstructed neonatal murine kidneys, we observed extratubular UMOD accumulation in the renal interstitium with tubular atrophy and leukocyte infiltrates. Finally, we found extratubular UMOD deposits associated with peritubular leukocyte infiltration in kidneys from patients with inflammatory kidney diseases. Taken together, we identified extratubular pUMOD as a strong inducer of leukocyte recruitment, underlining its critical role in mounting an inflammatory response in various kidneys pathologies.